2021
DOI: 10.3389/fimmu.2021.765528
|View full text |Cite
|
Sign up to set email alerts
|

Potential Association Between Dietary Fibre and Humoral Response to the Seasonal Influenza Vaccine

Abstract: Influenza vaccination is an effective public health measure to reduce the risk of influenza illness, particularly when the vaccine is well matched to circulating strains. Notwithstanding, the efficacy of influenza vaccination varies greatly among vaccinees due to largely unknown immunological determinants, thereby dampening population-wide protection. Here, we report that dietary fibre may play a significant role in humoral vaccine responses. We found dietary fibre intake and the abundance of fibre-fermenting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 40 publications
(58 reference statements)
1
5
0
Order By: Relevance
“…Lin et al [56] discovered that antibiotic exposure for at least seven days during the first two years of a child's life was positively correlated (p < 0.01) with chicken pox disease incidence, regardless of chicken pox vaccination status. Similar results were emulated in the murine model, where various types of antibiotic treatment and durations of exposure lead to decreased vaccine immunogenicity along with decreased gut microbiota diversity [57][58][59][60].…”
Section: Gut Dysbiosis and Its Influence On Vaccine Efficacy In Human...supporting
confidence: 69%
“…Lin et al [56] discovered that antibiotic exposure for at least seven days during the first two years of a child's life was positively correlated (p < 0.01) with chicken pox disease incidence, regardless of chicken pox vaccination status. Similar results were emulated in the murine model, where various types of antibiotic treatment and durations of exposure lead to decreased vaccine immunogenicity along with decreased gut microbiota diversity [57][58][59][60].…”
Section: Gut Dysbiosis and Its Influence On Vaccine Efficacy In Human...supporting
confidence: 69%
“… 50 A recent study has observed that microbial-derived SCFAs improve the humoral immune response to seasonal influenza vaccine. 51 Fecal concentrations of SCFAs are significantly lower in COVID-19 patients, and SARS-CoV-2 infection may be related to the impaired capacity for SCFA production. 52 In the present study, we observed that several SCFAs displayed a slight but nonsignificant decrease after the BBIBP-CorV vaccination.…”
Section: Discussionmentioning
confidence: 94%
“…In current literature, certain in vitro models have demonstrated the pro-viral effects of exogenous butyrate in viral replication due to their known role as a histone deacetylase inhibitor (HDAC) and effects on the type I IFN response ( Chemudupati et al., 2020 ). However, exogenous administration of butyrate has also been shown to enhance immune responses to various vaccines ( Sim et al., 2018 ; Cait et al., 2021 ; Wu et al., 2023 ). These contradicting effects may be due to the different types of SCFA administered, viruses and immortalized cell lines tested ( Wirusanti et al., 2022 ), but certainly highlights the importance of microbiome experimental models and the understanding of the gut microbiota and their derived metabolites in immunoregulation.…”
Section: Discussionmentioning
confidence: 99%